Development and characterization of optimized sustained release voriconazole-loaded chitosan nanoparticles for ocular delivery - Sahar Mohammadzadeh; Shadab Shahsavari; Farid Karimian; Seyed Jamal Hashemi; Hamid Akbari Javar; Hoda Mollabagher (Journal of Particle Science and Technology, 2021)
Voriconazole is an approved antifungal agent belonging to the triazole family. It is generally used for treating aggressive fungal infections such as invasive candidiasis or aspergillosis, as well as certain fungal infections, in immunocompromised patients. Voriconazole has an oral bioavailability of 96%, and patients can receive the medication either by oral or parenteral routes. To fabricate a topical ocular voriconazole delivery system, we prepared voriconazole-loaded chitosan nanoparticles by ionic gelation of chitosan with the addition of sodium tripolyphosphate (TPP). Three chitosan polymers with different molecular weights were tested by varying chitosan and TPP concentrations, and the produced nanoparticles were characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), and x-ray powder diffraction (XRD). The obtained data was presented into a Box-Behnken design, which showed a set of optimum parameters that would yield an optimized formulation with the most favourable properties. Subsequently, the optimized formulation was synthesized, and the voriconazole release from this formulation was monitored over 48 hr. Results showed the drug-loaded nanoparticles have high drug loading, show no burst effect, and sustain drug release for up to 48 hr. Therefore, this formulation is a potentially efficient ocular delivery system for voriconazole.